Production and Properties of Biosurfactant from Pectinatus cerevisiiphilus CT3 Isolated from Marine Sediments - SAENGE CHOOKLIN, Chanika; SAIMMAI, Atipan (Walailak Journal of Science and Technology (WJST), 2020)
A marine bacterial isolate, Pectinatus cerevisiiphilus CT3, was able to grow and produce biosurfactant on minimal salts media using glucose and NaNO3 as carbon and nitrogen sources. It was found that cellular growth and biosurfactant production in MSM were greatly affected by the medium components. After 54 h of cultivation, P. cerevisiiphilus CT3 was able to grow and produce surfactant, reducing the surface tension of the medium to 28.0 mN/m with a biosurfactant concentration of 3.05 g/l and a critical micelle concentration of 10 mg/l. Biosurfactant recovery by chloroform/methanol extraction showed pH and thermal stability with respect to surface tension reduction. It also showed emulsification activity and a high level of salt concentration. In addition, promising antimicrobial activity was revealed when tested against human pathogenic bacterial and fungal isolates. Based on these results, the isolated biosurfactant from the marine bacteria P. cerevisiiphilus CT3 revealed a broad physicochemical stability and has excellent antimicrobial properties, indicating the potential for possible use in various therapeutic and biomedical applications.